Economical analysis of project management under consideration of multi‐criteria decisions - Peldschus, Friedel (Technological and Economic Development of Economy, 2006)
“Economical analysis of project management under consideration of multi‐criteria decisions” Technological and Economic Development of Economy, 12(3), p. 169-170. First Published Online: 21 Oct 2010